RENAL CELL CARCINOMA WITH FACIAL SWELLING AND NASAL OBSTRUCTION AS PRIMARY PRESENTATION - Mohd Sabri, Mohd Naqib; Alli, Kasumawati; Lam, Sze Yin; Abdul Kadir, Kharul Azmi; Bahari, Norafida (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Background: Renal cell carcinoma (RCC) is a slow growing tumor. About 25–30% of patients are found to have metastases at diagnosis commonly to lung, liver and bones. The incidence of renal cell carcinoma metastasizing to the head and neck has been reported to range from 15-30%. Intranasal mass, or occasionally orbital mass maybe the presenting symptom of metastatic renal cell carcinoma to the nose and sinuses. Case presentation: We report a case of left RCC with large metastases to the frontonasal region producing head and neck symptoms before the primary lesion could be detected. Clinical presentations of metastatic RCC to the nasal and paranasal regions varies from recurrent epistaxis, nasal obstruction, facial pain, induration or even an orbital mass. In our case, although the patient had typical presentation of metastatic nasal tumour, the diagnosis of metastatic disease was not made. Conclusion: Patient presented with nasal and paranasal region tumour with no other systemic symptoms, presence of metastatic disease particularly from renal cell carcinoma should be included in diagnosis, as it is a slow growing tumour and the fact that nasal and paranasal areas are the most commonly affected site of metastatic RCC in the head and neck region.